2006
DOI: 10.3341/kjo.2006.20.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes in Correction of Brown Syndrome

Abstract: PurposeTo evaluate the outcomes of surgery for Brown syndrome.MethodsWe reviewed the charts of 15 patients who underwent surgery for Brown syndrome. The limitation of elevation in adduction (LEA) ranged from -2 to -4 degrees. A superior oblique muscle (SO) tenotomy was performed in 4 patients, a silicone expander was inserted in the SO of 9 patients, and a SO recession was performed in 2 patients. The results of surgery were analyzed with a follow-up period of more than 6 months, 42.3±48.42 months on average.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In Dubinsky-Pertzov's study, 9 patients were men (52.9%) and 8 were women (47.1%), and Sekeroglu et al (5) reported 18 (40.9%) men and 26 (59.1%) women patients (4). Various rates have been found of the involvement of the eye; of 60% left eye (6) versus 40% right eye, 19 (43.2%) right eye versus 25 (56.8%) left eye (5), and nine left eye affected of 15 patients (7). In our study, 98 (47%) right eyes were affected versus 92 (43%) left eyes.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In Dubinsky-Pertzov's study, 9 patients were men (52.9%) and 8 were women (47.1%), and Sekeroglu et al (5) reported 18 (40.9%) men and 26 (59.1%) women patients (4). Various rates have been found of the involvement of the eye; of 60% left eye (6) versus 40% right eye, 19 (43.2%) right eye versus 25 (56.8%) left eye (5), and nine left eye affected of 15 patients (7). In our study, 98 (47%) right eyes were affected versus 92 (43%) left eyes.…”
Section: Discussionsupporting
confidence: 44%
“…In our study, tenotomy was the most frequently performed surgical procedure (52.6% tenotomy, 40.5% nasal tenotomy, and 12.1% temporal tenotomy). Inferior oblique muscle overaction (IOOA) frequently occurred after a tenotomy or tenectomy procedure of SO (11). Post-operative SO palsy and IOOA occurred in 20% of our study group.…”
Section: Discussionmentioning
confidence: 79%
“…Yazdian et al 9 reported that 4 of 25 (16%) patients with Brown syndrome underwent horizontal rectus muscle surgery for correction of horizontal strabismus in addition to superior oblique weakening; however, no further details were provided regarding the type and extent of the deviations or the procedures performed. Cho et al 10 reported an even higher percentage of horizontal deviations in Brown syndrome, recording that 12 of 15 patients (80%) in their study had horizontal misalignment; 47% (7 of 15) exodeviations of 10 to 30 PD and 33% (5 of 15) esodeviations of 8 to 20 PD. 10 Fifty-four percent (8 of 15) of patients underwent horizontal rectus muscle surgery in addition to superior oblique tendon weakening.…”
Section: Discussionmentioning
confidence: 78%
“…Cho et al 10 reported an even higher percentage of horizontal deviations in Brown syndrome, recording that 12 of 15 patients (80%) in their study had horizontal misalignment; 47% (7 of 15) exodeviations of 10 to 30 PD and 33% (5 of 15) esodeviations of 8 to 20 PD. 10 Fifty-four percent (8 of 15) of patients underwent horizontal rectus muscle surgery in addition to superior oblique tendon weakening. Similarly, in our study, 8 of 16 (50%) patients with congenital Brown syndrome had significant primary position misalignment, most commonly exotropia (up to 30 PD), requiring surgical correction.…”
Section: Discussionmentioning
confidence: 78%
“…1 Indications for surgery include presence of abnormal head posture and hypotropia in primary position. 2 Many procedures have been suggested for treatment of Brown syndrome (Table 1). Superior oblique tenotomy is one of the most popular procedures, its major advantage being that the operation is technically simple and fast compared with other superior oblique weakening procedures; the drawback of this technique is the possibility of iatrogenic superior oblique palsy with overcorrection, which may be irreversible.…”
mentioning
confidence: 99%